Benzimidazole-Quinoline Hybrid Scaffold as Promising Pharmacological Agents: A Review. (14th September 2022) - Tiglani, Devleena; Salahuddin,; Mazumder, Avijit; Yar, Mohammad Shahar; Kumar, Rajnish; Ahsan, Mohamed Jawed
Abstract: Benzimidazole and quinoline showed a large spectrum of activities in various pharmacological fields like anticonvulsant, antimicrobial, and antimalarial, including antiviral and anticancer also. The different pharmacologically active series gained the attention of many researchers, which resulted in different hybrid structure of benzimidazole and quinoline. These synthesized compounds showed positive results against different diseases. Quinoline and benzimidazole can either be fused or incorporated using either functional groups/bonds. Medicinal chemists predicted that these moieties could be interconnected to yield a novel or modified hybrid compound. This review summarized Benzimidazole – Quinoline hybrids with their biological activities. Abstract : UF0001